AN ANALYSIS OF SARCASM IN THE LAST WEEK TONIGHT WITH JOHN OLIVER TALK SHOW - Ssa'addah, Yulia; Sari, Dian Purnama (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2025)
This study investigates the types and functions of sarcasm in Last Week Tonight with John Oliver, a talk show that blends humor and political commentary. Sarcasm is a rhetorical strategy often used to express irony, ridicule, and criticism, allowing speakers to indirectly highlight contradictions while engaging audiences through humor. Despite its frequent use in media discourse, few studies have systematically analyzed sarcasm in international political talk shows. Therefore, this research aims to examine the types and functions of sarcasm in John Oliver’s program.The study employed a qualitative descriptive method with an intralingual approach. Data were collected from five purposively selected episodes aired between May 2024 and May 2025. The episodes were transcribed, and sarcastic utterances were identified, coded, and classified using Camp’s (2011) theory of sarcasm types and Keraf’s (2008) framework of functions.The findings reveal 44 sarcastic utterances, dominated by propositional and illocutionary types, with comparison as the most frequent function. These results suggest that sarcasm in Last Week Tonight serves a dual role: entertaining viewers while functioning as a rhetorical device to criticize social and political issues.